From bench to bedside: Calprotectin (S100A8/S100A9) as a biomarker in rheumatoid arthritis - Inciarte-Mundo, José; Frade-Sosa, Beatriz; Sanmartí, Raimon (Frontiers in Immunology, 2022)
S100A9/S100A8 (calprotectin), a member of the S100 protein family, has been shown to play a pivotal role in innate immunity activation. Calprotectin plays a critical role in the pathogenesis of rheumatoid arthritis (RA), as it triggers chemotaxis, phagocyte migration and modulation of neutrophils and macrophages. Higher calprotectin levels have been found in synovial fluid, plasma, and serum from RA patients. Recent studies have demonstrated better correlations between serum or plasma calprotectin and composite inflammatory disease activity indexes than c-reactive protein (CRP) or the erythrocyte sedimentation rate (ESR). Calprotectin serum levels decreased after treatment, independently of the DMARD type or strategy. Calprotectin has shown the strongest correlations with other sensitive techniques to detect inflammation, such as ultrasound. Calprotectin independently predicts radiographic progression. However, its value as a biomarker of treatment response and flare after tapering is unclear. This update reviews the current understanding of calprotectin in RA and discusses possible applications as a biomarker in clinical practice.